Energy-Aware Communications 17th International Workshop, EUNICE 2011, Dresden, Germany, September 5-7, 2011, Proceedings - Lehnert, Ralf (Information Systems and Applications, incl. Internet/Web, and HCI, 2011)
This book constitutes the refereed proceedings of the 17th EUNICE 2011 Workshop on energy-aware communications, held in Dresden, in September 2011. The proceedings comprise 16 full papers and 7 poster papers which are presented together with the abstracts of the 3 invited talks. The topics covered are: network architectures; ad-hoc and wireless networks; system simulation; network planning, optimization, and migration; traffic engineering; quality of experience; and energy efficient architectures.